IMPLEMENTASI KOMUNIKASI EDUKATIF DALAM PEMADUAN IMAN, ILMU DAN AMAL STUDI PEMBELAJARAN PAI DI SMA IT ABU BAKAR YOGYAKARTA - Andrianto Andrianto (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2019)
Abstract Educative communication in the integration of faith, science and charity is communication carried out by two or more people whose education is educational. And this communication is very good to be mastered by the teacher for the sake of the fluency of the students. The type of research used by the author is the type of qualitative research. The subjects of this study were PAI teachers and Abu Bakar High School IT students in Yogyakarta. Data collection is done by conducting observations, interviews, documentation and triangulation. Data analysis was carried out through four stages, namely: data clarification, data reduction, data interpretation and conclusion drawing. The technique of collecting data with the inductive method is to find as much data as possible and then conclude (general-specific) The results of this study are: 1) the concept of characteristics and implementation of educational communication in the integration of faith, science and charity. Study of PAI Learning in Abu Bakar High School IT Yogyakarta, so a teacher must prepare teaching materials and a teacher must be able to explain and be able to master the material taught in the classroom, and a teacher must be able to provide examples in daily life so students easily understand the content of the material taught and the concepts in PAI learning refer to the JSIT curriculum and the merger of services for example by combining faith, science and charity in everyday life. 2) implementation of educational communication in the integration of faith, science and charity. PAI learning study at Abu Bakar High School IT Yogyakarta, the implementation is at 7:30 all students are already in class and reading the prayer and tadarus of the Qur'an, every Friday for those who are obliged to pray Friday, fasting Monday Thursday, eat together, hold a big day commemoration such as the lightning boarding school in the month of Ramadhon, social charity services and at Abu Bakar IT High School Yogyakarta do not know every day there are Islamic programs, Islamic art of calligraphy, recitations, hadroh, nasid, and there is religious mentoring and Boarding Scool, Full Day, Extracurricular, sports, robotics, journals, scouts (scouting), mentoring to support faith, science and charity. 3) the contribution of educational institutions in the implementation of educational communication in the integration of faith, science and charity. PAI learning studies at Abu Bakar High School IT Yogyakarta, the contribution of the concept is clearly KYM, namely noble foundation consortium escorts and manages the foundation from the concept of learning, Islam becomes the main spirit in Abu Bakar High School IT Yogyakarta so all teachers such as PAI teachers and from elementary, junior high, high school, the foundation is how to manage in terms of management, facilities, all R & D who take care of foundations are very helpful and learning activities. Keywords: Educational Communication, Integration of Faith, Science and Charit.